Assessing the preference heterogeneity in marine ecotourism attributes by using choice experiment - Yacob, Mohd Rusli; Shuib, Ahmad (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
This paper aims to assist marine parks managers or policy makers in operating and managing of ecotourism resources in accordance with the concept of sustainable ecotourism development, by providing results of a valuation study on the marine parks. A choice experiment is employed to estimate the values of changes in marine ecotourism resources. The attributes investigated were ecological management (EM), recreational activity congestion (RAC), provision employment to local people (ELP) and conservation charge (CC). The general, specific and interactions of conditional logit (CL) and mixed logit (MLM) models are estimated to account for heterogeneity in the preferences of the visitors from the various management options of marine ecotourism attributes. The findings reveal that there is considerable preference heterogeneity among visitors. Findings of this study can assist marine parks manager in design ecotourism management policies for sustainable marine ecotourism development in marine parks with possible implications for other marine parks in Malaysia.